COMMUNICATING PERCEIVED BARRIERS TO ADOPTING NASOPHARYNGEAL CANCER PREVENTIVE BEHAVIOUR - Ho, Jia Yiing; Ting, Su Hie; Yuwana, Podin (2021)
The study investigated how the public communicate their perceived barriers to adopting the preventive behaviour to minimise risk of Nasopharyngeal cancer (NPC), also known as nose and throat cancer. The study involved 65 participants living in Kuching and Samarahan divisions of Sarawak, Malaysia. Semi-structured interviews were conducted to explore their perceived barriers after reading an NPC pamphlet produced by the Ministry of Health, Malaysia. The participants reported that living a healthy lifestyle is more difficult than consulting a doctor. A total of 19% participants reported that living a healthy lifestyle is hard, 29% remained indifferent and 52% found it easy. They knew NPC risk could be minimised by reducing smoking, following a healthy diet and exercising. However, the main perceived barrier was a lack of discipline. For 69% of the participants, seeing a doctor about NPC was not a barrier, but the remaining participants fear of facing the truth and the pain of the cancer screening. The findings suggest that in the context of NPC, recommendations to consult doctors should be more visibly worded to attract the public’s attention and to motivate action to seek medical treatment.